Ways to Teach Students to Independent, Creative Thinking - Gulnara Israilova; Sayyora Sheraliyeva (International Journal on Human-Computing Studies, 2021)
Independent learning is a critical learning strategy in higher education. Independent education - when successfully completed, students' independence is nurtured. This article describes the problem of increasing the self – activity of the assimilation of knowledge independent thinking by organizing self – education in higher educational institutions